EFEKTIVITAS KONSENTRASI DAN LAMA PERENDAMAN AIR KELAPA HIJAU TERHADAP PERTUMBUHAN AWAL MATA TUNAS BUD CHIPS TEBU (Saccharum officinarum L.) VARIETAS PS 881 - Danil Budairi Firmansyah; M. Darul Anwar; Nur Fitriyah (Universitas Islam Kadiri, 2020)
ABSTRACT Sugar cane (Saccharum officinarum L.) is an important commodity as a raw material for making sugar. This is because sugarcane contains 20% sugar liquid. Along with the increasing population of Indonesia, the need for sugar continues to increase, but the increase has not been offset by domestic sugar production. Problems that often arise in the low production of sugar include in terms of sugarcane cultivation, namely the preparation of seeds, seed quality and varieties used. For this reason, the preparation of quality and fast seeds is needed to increase production by using the budchip method by adding ZPT young green coconut water. The purpose of this study is to find out the effect of the combination of concentration and immersion duration of green coconut water on bud eye growth of sugarcane budchip (Saccharum officinarum L.) buds of PS 881 variety and carried out on the joyorosan cv land of the tiru kidul village, Kediri district. This research uses RAKF (Randomized Factorial Design) with 9 treatments, namely K1L1 (concentration 25% + soaked 2 hours), K1L2 (concentration 25% + soaked 4 hours), K1L3 (25% concentration + soaked 6 hours) K2L1 (concentration 50% % + soaked 2 hours), K2L2 (50% concentration + soaked 4 hours), K2L3 (50% concentration + soaked 6 hours), K3L1 (75% concentration + soaked 2 hours), K3L2 (75% concentration + soaked 4 hours) , K3L3 (75% concentration + soaked for 6 hours). From the results of the study showed that the overall treatment of the combination of concentration and immersion of coconut water showed no real results. In a single factor the concentration on the percentage of growth parameters and the number of roots there is a real influence. At a concentration of 50% it is able to stimulate the growth of sugarcane shoots due to the adequacy of the cytokinin and auxin hormones while at a concentration of 25% there is not enough hormone to be able to stimulate growth. In the observation of plant height, stem diameter, number of leaves, bassah weight did not significantly affect both the combination and the single factor. This is due to the improper immersion duration interval. according to, there is a certain time where the growth of plant growth is very active and fast in taking nutrients so that the exchange of substances takes place very intensively. Keywords: Budchip, Cane, Green Coconut water, Concentration, Soaking time